Transcriptomic signatures responding to PKM2 activator TEPP-46 in the hyperglycemic human renal proximal epithelial tubular cells - Wang, Zhimin; Yu, Jiating; Hao, Dan; Liu, Xin; Wang, Xiao (Frontiers in Endocrinology, 2022)
Pyruvate kinase M2 (PKM2), as the terminal and last rate-limiting enzyme of the glycolytic pathway, is an ideal enzyme for regulating metabolic phenotype. PKM2 tetramer activation has shown a protective role against diabetic kidney disease (DKD). However, the molecular mechanisms involved in diabetic tubular has not been investigated so far. In this study, we performed transcriptome gene expression profiling in human renal proximal tubular epithelial cell line (HK-2 cells) treated with 25-mM high D-glucose (HG) for 7 days before the addition of 10-μM TEPP-46, an activator of PKM2 tetramerization, for a further 1 day in the presence of HG. Afterwards, we analyzed the differentially expressed (DE) genes and investigated gene relationships based on weighted gene co-expression network analysis (WGCNA). The results showed that 2,902 DE genes were identified (adjusted P-value ≤ 0.05), where 2,509 DE genes (86.46%) were co-expressed in the key module. Four extremely down-regulated DE genes (HSPA8, HSPA2, HSPA1B and ARRB1) and three extremely up-regulated DE genes (GADD45A, IGFBP3 and SIAH1) enriched in the down-regulated endocytosis (hsa04144) and up-regulated p53 signaling pathway (hsa04115), respectively, were validated by the qRT-PCR experiments. The qRT-PCR results showed that the relative expression levels of HSPA8 (adjusted P-value = 4.45×10-34 & log2(FC) = -1.12), HSPA2 (adjusted P-value = 6.09×10-14 & log2(FC) = -1.27), HSPA1B (adjusted P-value = 1.14×10-11 & log2(FC) = -1.02) and ARRB1 (adjusted P-value = 2.60×10-5 & log2(FC) = -1.13) were significantly different (P-value < 0.05) from case group to control group. Furthermore, the interactions and predicted microRNAs of the key genes (HSPA8, HSPA2, HSPA1B and ARRB1) were visualized in networks. This study identified the key candidate transcriptomic biomarkers and biological pathways in the hyperglycemic HK-2 cells responding to the PKM2 activator TEPP-46 that can highlight a possibility of PKM2 tetramerization reshaping the interplay among endocytic trafficking through the versatile networks of Hsp70s, and rewiring the crosstalk between EGFR signal transduction circuits and metabolic stress to promote resilience, which will be valuable for further research on PKM2 in DKD.